Explorations and Encounters in French - Fornasiero, Jean; Mrowa-Hopkins, Colette (University of Adelaide Press, 2010)
With a title derived literally from the explorations of the French in the Pacific and metaphorically from classroom encounters with another culture-both of which form important subsections to the volume-Explorations and Encounters in French actively seeks to unite those fields of enquiry sometimes seen as separate, namely, culture and language. The essays selected for inclusion in Explorations and Encounters in French bring together many of the current research strands in French Studies today, tapping into current pedagogical trends, analysing contemporary events in France, examining the Franco-Australian past, while reviewing teaching practice and the culture of teaching. Collectively, the essays reflect the common engagement with language, culture and society that characterizes the community of French teachers and scholars in Australia and abroad.